The problem of operation control of fuel utilization in steam - boilers - Chepurnyi, M. M.; Popov, O. Ya.; Pishenina, N. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The results of calculation for dertermination of surplus air factor, loss of heat due to chemical incompleteness of combustion and loss of heat due to waste gases are stated. Graphs for determination of these values are constructed.